Enriching Arabic Vocabulary: Examining the Impact of Quranic Word-by-Word Translation on Student Proficiency - Erna Herawati; Ainil Mawaddah (Pustaka Peradaban, 2023)
This study investigates the significance of using word-by-word translations of the Qur’an to enhance Arabic language learning and expand students’ vocabulary. Employing a literature review approach, this research gathers pertinent data from academic sources related to the subject. The collected data is analyzed using content analysis techniques. Findings from the literature review demonstrate that utilizing word-by-word translations of the Qur’an aids students in comprehending Arabic words more effectively, thereby improving their capacity to memorize and apply Arabic vocabulary. Additionally, such translations can expedite the Arabic learning process, given the Qur’an’s prominent role as a primary Arabic source. However, it’s important to note that reliance solely on translation might curtail students’ holistic understanding of Arabic and foster dependency on translation. Thus, the proper and discerning use of word-by-word Qur’an translations is crucial to avoid diminishing students’ comprehensive grasp of Arabic. In conclusion, word-by-word translation of the Qur’an holds importance in enhancing Arabic language learning and vocabulary expansion among students, but its application should be judicious. This study contributes to the evolution of Arabic curriculum and pedagogical methods.